Development of Website-Based Teaching Materials with a Multi-Representation Approach Assisted by Scratch Simulation in Circular Motion - Yulita Nurbaiti; Wahyu Hardyanto; Suharto Linuwih (Physics Communication, 2025)
This study is an R&D research that aims to describe the feasibility and characteristics of website-based teaching materials with a multi-representation approach assisted by Scratch simulation in a circular motion. The development model used in this study was a 4-D development model, (define, design, develop, disseminate). The define stage consists of the draft instrument, learning objectives flow (ATP), analysis and learning modules, and analysis journal. The design stage consists of teaching materials design and instrument expert validation design for evaluating the teaching materials. The development stage consists of developing instruments for assessing the digital teaching, teaching materials prototype, and expert validation and revisions based on the results of expert validation. The dissemination stage consists of the final validation consisting of the results of the final validation of the product and the dissemination of teaching materials through the publication of scientific papers in journals.  Based on the results of expert validation, the percentage of average of score on the material aspect is 91.25% with a very feasible category. The percentage of an average score on the media aspect is 92.82% with the very feasible category. The readability percentage of teaching materials has an average value of 87.59% in the easy-to-understand category. The percentage of teacher and student responses was 97.50% and 88.61% in the very good category response.